KKN tematik : creative economic digital dalam implementasi MBKM - Riril Mardiana Firdaus; Lilik Sri Hariani; Walipah Walipah; Naim Naim; Udik Yudiono (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
The aim of MBKM is to encourage students to master various fields of science with their fields of expertise. This policy gives students the opportunity to choose the courses they will take based on their own wishes. The implementation of the Independent Learning Campus policy encourages the learning process in higher education to be more autonomous and flexible. Not only highly educated but able to become agents of change in small and large scope. The resulting changes and innovations are able to make a maximum contribution to the progress of a nation that has quality human resources. In general, this research is based on the principles of descriptive analytic/descriptive analysis. The results of the research that has been done, namely about the implementation of independent learning on an independent campus to support the creative digital economy of students, obtained good results in terms of understanding and implementation in the field when carrying out assistance in downstreaming processed food products for rural communities.